Animal Genetic Resources for Sustainable Livestock Development in Nepal - Neopane, Shreeram P. (Nepalese Journal of Agricultural Sciences, 2026)
Nepal is rich in animal genetic resources (AnGR) both in terms of diversity and numbers. Animal genetic resources play a key role in livestock development in the country mainly through their contribution to income generation and livelihood enhancement. They have also non-economic values (socio and cultural values) or bequest value, which doesn’t seem to be valued. The diversity both species and breeds levels are enormous in the country. A total of 25 indigenous breeds from seven livestock species have been characterized so far. There are several transboundary breeds (regional and international) in the country. Despite of these several breeds, particularly indigenous breeds are declining making system non-sustainable. The major threats for animal genetic resources are genetic erosion, indiscriminate crossbreeding, low productivity, small holding size, lack of specific policies, changing production systems, lack of valuation of local breeds, increasing competition for natural resources and environmental degradation. These factors are contributing to genetic erosion of indigenous breeds in the country. Several breeds have population declined and few are about to be extinct if careful measures are not taken. Strategic actions should be undertaken in order to check genetic erosion and improve their contribution. Effective management of AnGR will address these constraints precisely. Management for AnGR includes its understanding (characterization), using (utilization), maintaining (conservation), accessing and benefit sharing.